Pengaruh Kepemilikan Manajerial, Kepemilikan Institusional, Kebijakan Dividen, Kebijakan Hutang, Dan Ukuran perusahaan Terhadap Nilai Perusahaan (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2015) - Hartini, Sri, Yuli Tri Cahyono, M.M.,Akt, CA (2017)
The purposeof this research is to analyze that effect of managerial ownership,institutional ownership, dividend policy, debt policy, and the size of the company on firm value. The company's value in this study is proxied by Price Book Value (PBV.Population of this research are manufacturing companies listed in Indonesia Stock Exchange in 2012-2015. Samples were taken by using purposive sampling technique and the total of 61 companies for four years in accordance with the criteria. Analysis techniques using classic assumption test and multiple regression analysis. The result of the study shows that the managerial ownership, and size of the company have significant influence the value of the company, while institutional ownership, dividend policy, debt policy do not have influence the value of the company. Keywords: managerial ownership, institutional ownership, dividend policy, debt policy, the size of the company, the company's value.